2011
DOI: 10.1111/j.1439-0531.2011.01885.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Vitrification of Feline Ovarian Cortex on Follicular and Oocyte Quality and Competence

Abstract: Cryopreservation of ovarian cortex has important implications in the preservation of fertility and biodiversity in animal species. Slow freezing of cat ovarian tissue resulted in the preservation of follicular morphology and in the follicular development after xenografting. Vitrification has been recently applied to ovarian tissues of different species, but no information is available on the effect of this method on feline ovarian cortex. Moreover, meiotic competence of fully grown oocytes isolated from cryopr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
21
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(23 citation statements)
references
References 30 publications
1
21
1
Order By: Relevance
“…() reported that ovarian fragments with dimensions of 10 mm (length) × 3 (thick) × 2 mm (width) presented 56% of morphologically intact follicles, while the fragments of 10 mm × 3 mm × 4 mm presented 34% of intact follicles. Previous investigations on the cryopreservation of feline ovarian tissue used only fragment sizes that were cut up to 27 mm 3 (Alves et al., ; Luvoni et al., ; Tanpradit, Comizzoli, Srisuwatanasagul, & Chatdarong, ), probably based on cryobiology principles (Neto et al., ). An ovarian tissue fragment of approximately 1–2 mm thickness favours the larger contact area and, consequently, higher solute penetration (Newton, Aubard, Rutherford, Sharma, & Gosden, ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…() reported that ovarian fragments with dimensions of 10 mm (length) × 3 (thick) × 2 mm (width) presented 56% of morphologically intact follicles, while the fragments of 10 mm × 3 mm × 4 mm presented 34% of intact follicles. Previous investigations on the cryopreservation of feline ovarian tissue used only fragment sizes that were cut up to 27 mm 3 (Alves et al., ; Luvoni et al., ; Tanpradit, Comizzoli, Srisuwatanasagul, & Chatdarong, ), probably based on cryobiology principles (Neto et al., ). An ovarian tissue fragment of approximately 1–2 mm thickness favours the larger contact area and, consequently, higher solute penetration (Newton, Aubard, Rutherford, Sharma, & Gosden, ).…”
Section: Discussionmentioning
confidence: 99%
“…Studies on felines, mice and humans, have demonstrated that the follicles presented in the ovarian tissue are able to survive during freezing and thawing, and are capable to develop from early to more advanced stages (Bosch et al., ; Gosden, Boulton, Grant, & Webb, ; Oktay, Newnton, Mullan, & Gosden, ). In cats, it has been demonstrated that vitrification was superior for preserving follicular original structure and viability compared to slow freezing (Comizzoli, Martinez‐Madrid, Pukazhenthi, & Wildt, ) and that oocytes recovered from vitrified‐warmed ovarian tissue are capable of resuming meiosis when cryopreserved in cryotubes (Luvoni et al., ) or in cryotop (Alves, Kozel, & Luvoni, ).…”
Section: Introductionmentioning
confidence: 99%
“…Bosch et al [14] reported the survival of cat ovarian tissue after xenotransplantation into nude mice, whereas Lima et al [19] and Luvoni et al [20] assessed the post-thawed survival of cat ovarian tissue by histological evaluation of follicular structure. Our group used BrdU-labeling and Hoechst staining for integrity assessment of mechanical isolated preantral follicles to control culture impacts [21], but it was shown that the procedure of isolation from the ovarian cortex itself can cause a loss of integrity in primordial follicles [22].…”
Section: Discussionmentioning
confidence: 99%
“…In contrast to Bosch et al [14] we didn’t perform xenotransplantation of frozen-thawed tissue, but after one week culture still a high amount of follicles were detectable. Other authors vitrified the tissue [20] and reported the survival of oocytes after thawing again without performing culture examination. Therefore, it is very difficult to compare the results and conclude about the best freezing approach for cat species.…”
Section: Discussionmentioning
confidence: 99%
“…We firstly demonstrated that feline immature oocytes retrieved from vitrified ovarian tissue ( in situ oocytes ) maintain the capability of resuming meiosis after warming (Luvoni et al. ). Evaluation of cytoskeletal and chromatin organization after vitrification indicated that damage to cytoskeleton occurred mainly to actin rather than to the tubulin network, but GV morphology was not altered.…”
Section: Introductionmentioning
confidence: 99%